The efficacy and tolerability of mirabegron in a non-trial clinical setting. (May 2016) - Balachandran, Aswini; Duckett, Jonathan
Abstract: Objectives: Mirabegron is the first β3 -adrenoceptor selective agonist approved for the treatment of OAB. Many randomised controlled trials report outcomes that are difficult to interpret in usual clinical practice. The aim of our study is to evaluate the efficacy and tolerability of mirabegron as treatment option for OAB in an unselected patient population in daily clinical practice and to identify if any patient characteristics predicted patients response to therapy. Study design: A prospective consecutive cohort of patients was studied between February 2013 and July 2014. Patients were prescribed Mirabegron 50 mg once daily for 6 weeks. They were assessed at the initial appointment and at 6 weeks using validated questionnaires. The primary outcome measure was defined using the Patient Global Impression of Improvement Scale (PGI-I). Results: 317 women were prescribed mirabegron and 244 (77%) completed 6 weeks of drug therapy. Of those completing the course, 27 (11%) described themselves as "very much better" and a further 56 (23%) much better. There was significant symptom improvement based on the ICIQ-FLUTS long form scores from 19.7 to 16.2 ( p < 0.001) and urinary distress inventory from 68.6 to 61.3 ( p < 0.005). Twenty-three (8.6%) patients discontinued mirabegron prematurely due to side-effects. Thirty one (10%) did not attend follow up and 19 (6%) decided against taking the medication and did not use their prescription. Conclusion: Mirabegron is a treatment option for patients with overactive bladder. Treatment benefits are modest but the discontinuation rate for side effects are low.